2013
DOI: 10.1063/1.4839555
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional diamond detectors: Charge collection efficiency of graphitic electrodes

Abstract: Implementation of 3D-architectures in diamond detectors promises to achieve unreached performances in the radiation-harsh environment of future high-energy physics experiments. This work reports on the collection efficiency under β-irradiation of graphitic 3D-electrodes, created by laser pulses in the domains of nanoseconds (ns-made-sensors) and femtoseconds (fs-made-sensors). Full collection is achieved with the fs-made-sensors, while a loss of 25%–30% is found for the ns-made-sensors. The peculiar behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 15 publications
1
55
0
Order By: Relevance
“…The structural modification generated, as identified through Raman microspectroscopy is revealed as graphitic and amorphous sp 2 bonded carbon intermixed with sp 3 bonded diamond 26,27 , while it has recently been shown that, in addition, the NV concentration may be enhanced in nearby regions 28 . When the laser focus is traced through the diamond, a continuous damage track is created which is electrically conductive 29,31 , and has been successfully used for a range of radiation detectors [32][33][34] . Transmission electron microscopy and electron energy loss spectroscopy has been used to study thin slices of the laser-modified area, showing the presence of sub-micrometer patches of sp 2 bonded amorphous carbon, in addition to multiple dislocations of the diamond lattice 30 .…”
mentioning
confidence: 99%
“…The structural modification generated, as identified through Raman microspectroscopy is revealed as graphitic and amorphous sp 2 bonded carbon intermixed with sp 3 bonded diamond 26,27 , while it has recently been shown that, in addition, the NV concentration may be enhanced in nearby regions 28 . When the laser focus is traced through the diamond, a continuous damage track is created which is electrically conductive 29,31 , and has been successfully used for a range of radiation detectors [32][33][34] . Transmission electron microscopy and electron energy loss spectroscopy has been used to study thin slices of the laser-modified area, showing the presence of sub-micrometer patches of sp 2 bonded amorphous carbon, in addition to multiple dislocations of the diamond lattice 30 .…”
mentioning
confidence: 99%
“…A smaller electrodes distance increases the amount of generated charge that could be collected before trapping giving rise to a higher charge collection efficiency with a lower saturation voltage (Fig. 2, right) [16].The full collection efficiency of β-induced signals for a 3D diamond detector fabricated in a 500 μm thick diamond substrate is reached at voltages about ten times lower than for a 2D sensor made of the same diamond substrate [13]. This is an important advantage for 3D detectors because high full collection efficiency voltages are generated by high accuracy high voltage source meters which are very expensive and usually bulky.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, even if it is assumed that all the regions identified as sp 2 are continuous along the wire and can hence contribute to any DC conductivity, values for the intrinsic structural resistivity are expected to be over an order of magnitude lower than those previously reported for laser written wires. [18][19][20]25,26 The relatively low sp 2 content of even the patches in Fig. 3(e) is surprising, and at no point, purely graphenic EELS spectra are recorded.…”
mentioning
confidence: 99%
“…However, previous Raman studies revealed only the partial formation of sp 2 bonded graphite within the laser irradiated zones. 14,19,23,24 When using such modifications to create wires, the resultant resistivity varies from 0.02 to 2 X cm, [18][19][20]25,26 with values at least an order of magnitude higher than that for polycrystalline graphite. 27 Similarly, when writing optical waveguides using the stress field generated by modifications in Regime (ii), the propagation losses are significantly lower than those expected from a complete conversion of the irradiated zones to graphite.…”
mentioning
confidence: 99%
See 1 more Smart Citation